2006
DOI: 10.3327/jnst.43.699
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop Experiments using Tight-Lattice 37-Rod Bundles

Abstract: In order to design a Reduced-Moderation Water Reactor (RMWR) core from a thermal-hydraulic point of view, an evaluation method on the pressure drop in a tight-lattice rod bundle is required. In this study, axial pressure drops in tight-lattice 37-rod bundles were measured under conditions of 2-9 MPa in exit pressure and 200-1,000 kg/(m 2 Ás) in mass velocity. The measured pressure drops were compared with calculated ones by the evaluation method with the Martinelli-Nelson's correlation. The comparison shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Confirmation to the prediction method for the pressure drop in the tight lattice rod bundles under steady state. For the pressure drop in the tight lattice rod bundles under steady state, JAEA seven-rod [12], 37-rod bundle [13] data and Toshiba seven-rod [14] and 14-rod [15] data were derived. The research showed the Martinelli-Nelson two-phase flow multiplifier [16] being applicable to the tight lattice rod bundles within an accuracy of ±10%.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation to the prediction method for the pressure drop in the tight lattice rod bundles under steady state. For the pressure drop in the tight lattice rod bundles under steady state, JAEA seven-rod [12], 37-rod bundle [13] data and Toshiba seven-rod [14] and 14-rod [15] data were derived. The research showed the Martinelli-Nelson two-phase flow multiplifier [16] being applicable to the tight lattice rod bundles within an accuracy of ±10%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, two-phase flow analysis for the dense-lattice bundle or narrow channel is needed, and the acquisition of experimental data and the modeling of the flow have been done in the past several years. Tamai et al (2006) evaluated the effect of the gap width and the power profile from the pressure drop measured in dense-lattice 37 rod bundles. Sadatomi et al (2007) studied the void fraction in a double subchannel with dense-lattice array and the data was compared with some correlations and subchannel codes.…”
Section: Introductionmentioning
confidence: 99%
“…The void fraction distribution affects not only the BT but pressure drop and reactor characteristics. Therefore, JAEA carried out BT experiments with 37-rod bundles along with high pressure (2)(3)(4)(5) and void fraction experiments (6) . The purposes of the void fraction experiments were to elucidate liquid/vapor distribution and flow behavior in a tight-lattice rod bundle and to obtain a 3D void fraction database for the verification of a correlation and/or an advanced simulation code (7,8) .…”
Section: Introductionmentioning
confidence: 99%